2006
DOI: 10.1149/1.2160429
|View full text |Cite
|
Sign up to set email alerts
|

Micrometer-Scale Amorphous Si Thin-Film Electrodes Fabricated by Electron-Beam Deposition for Li-Ion Batteries

Abstract: A series of micrometer-scale Si thin films were fabricated by electron-beam deposition on the Cu substrate with specially treated concave-convex surface. The combined analyses involving scanning and transmission electron microscopy, selected area electron diffraction, and X-ray diffraction revealed that the deposited Si layer possessed good adhesion to the substrate and a discontinuous amorphous microstructure in which there existed large amounts of interface regions. The surface changes of the Si thin-film el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(104 citation statements)
references
References 32 publications
6
97
0
Order By: Relevance
“…27 This is because the large strain in the thick Si film during Li ϩ cycling severely pulverizes the film and causes loss of contact of part of the Si with the substrate, as illustrated in Figure 1a. Yin et al 28 have sputtered relatively thick a-Si film (thickness Ͼ2 m) on a roughened copper substrate and obtained improved performance. 19,26 To demonstrate the feasibility of CNT-Si films as effective anode material, we first made a CNT-Si composite film on a SS 500 mesh, as shown by the SEM image in Figure 2a (see Experimental Section for detailed procedures).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 This is because the large strain in the thick Si film during Li ϩ cycling severely pulverizes the film and causes loss of contact of part of the Si with the substrate, as illustrated in Figure 1a. Yin et al 28 have sputtered relatively thick a-Si film (thickness Ͼ2 m) on a roughened copper substrate and obtained improved performance. 19,26 To demonstrate the feasibility of CNT-Si films as effective anode material, we first made a CNT-Si composite film on a SS 500 mesh, as shown by the SEM image in Figure 2a (see Experimental Section for detailed procedures).…”
Section: Resultsmentioning
confidence: 99%
“…27Ϫ30 Islands and aggregates of Si particles were found on the substrates after a few battery cycles. 27,28 In Figure 5a, ripples caused by repeated Figure 5b is a SEM image taken at a broken edge of the CNT-Si film after 10 cycles, where CNTs sticking out of the edge can clearly be seen. Figure 5c is a SEM image of the composite film after 20 cycles.…”
Section: Incorporation Of Sinps Into the Cnt-si Filmsmentioning
confidence: 99%
“…An enabler for good adhesion between the expanding and contracting Li-Si [21][22][23][24][25][26][27] active material (and alloys of Li-Si-Sn 28 ) and the copper current collector is the roughened surface of the copper. In a related vein, Kim et al 29 found that the cycle performance of the silicon-graphite composite electrodes that were slurry-coated onto Cu foils was enhanced when a nodule-type copper foil was employed, similar to the morphology depicted in Figure 1.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…5,6 However, the huge volume change during the charge and discharge process can cause a pulverization of the electrode and electric disconnection from current collectors, resulting in poor cycling stability. To tackle this problem, a variety of carbon frameworks such as 0D hollow carbon spheres, 7 1D CNFs 8 and 2D graphene 9 were utilized to support Si nanoparticles.…”
Section: Introductionmentioning
confidence: 99%